Application of Making Moringa and Lemon Grass Tea to Reduce Hypertension in Denai Sarang Burung Village - Aulia, Destanul; Kurniawan Z, Teguh; Luthfiyyah, Suci Haya; Hutasuhut, Raihan Putri Dahlina; Azahra, Siti; Deannova, Alfito (Talenta Publisher, 2023)
A disease that has a high prevalence and reduces ` quality of life of sufferers is hypertension. Hypertension is also known as the silent killer, which sufferers often don't realize because there are no specific symptoms. Until now, hypertension is still a big challenge for Indonesia. The number of people with hypertension continues to increase every year and this disease is often found in primary health care. It turns out that in reducing hypertension, you can take advantage of plants that grow in the village which are rarely used by the local community, namely moringa leaf tea and lemongrass which grow along the area in the village near the bird's nest. The content of Moringa leaf tea with protein is two times higher than yogurt, vitamin A is seven times higher than carrots, potassium is three times higher than bananas, calcium is four times higher than milk, vitamin C is higher than oranges while lemongrass has a high citral content. capable of providing anti-inflammatory effects that are used to reduce hypertension